Determined by Christ: the Pauline metaphor "being in Christ" - Beyer, Barbara 198X- (Supplements to Novum Testamentum, 2024)
This study investigates the meaning and background of the apostle Paul's much used and highly debated 'in Christ' phrases by use of insights from Greek philology and metaphor theory.